A PERSONAL ENCOUNTER WITH RESEARCH: POETIC TRANSCRIPTION: Received: 16th September 2024, Revised: 24th October 2024, 6th November 2024, Accepted: 10th December 2024, Date of Publication: 29th April 2025 - Lorenzo Cherubini (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Poetic inquiry is a qualitative method that accounts for both the participants’ first-person perspectives and the researcher’s personal interpretation in a unique and invitational presentation of data. This paper will discuss, first, the use of poetic transcription to transform the Research Conversation interview scripts of Indigenous community members involved in a partnership with university educators. The research project examined the concepts of learning and education from those in the Indigenous community that were directly involved in the culturally appropriate programs offered at a Friendship Centre in Ontario (Canada). The key themes identified in the data will be shared. They include: 1. Education as a “lived reality” 2. Sense of Well-Being, and 3. Resolving Tensions. Second, the paper will present the respective poems that emerged from the poetic transcription that represent the researcher’s critical encounter with participants’ delicately complex stories. The manuscript addresses how readers’ emotions are implicated in poetic inquiry since the qualitative approach serves to appeal to the broader complexity of participants’ experiences. The poems, therefore, underscore the intensely personal encounter and individual impressions the researcher experienced and, in turn, offer readers an opportunity to share in the moments of the critical encounter.